"A thousand mad things before breakfast" : the interplay of reason and imagination in J.K. Rowling's Harry Potter Series - Dingle, Teresa Anne (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2020)
Realism and imagination serve roles in J.K. Rowling's world creation in the Harry Potter series and thus will be traced through this thesis. Both rational and imaginative thinking are modes of thought and play roles in characters' responses to issues. Further, reason and imagination are used in Harry Potter as modes of resistance against the prejudice which shapes much of the society of the magical world and so will be examined. In the Harry Potter series, Rowling combines fantasy traditions with realism and in so doing ensures her wizarding world mirrors the world of the reader. Rowling enacts a re-creation of the real world of the reader through a recombination of realistic and fantasy elements. This thesis will call on fantasy theorists Rosemary Jackson and Dimitra Fimi as well as the fantasy and science fiction writer Ursula Le Guin to examine how Rowling conforms to and expands on the fantasy tradition in which she writes in her creation of the magical world. It is made evident through Rowling's treatment of Harry's friends Hermione Granger and Luna Lovegood that combining reason and imagination is more beneficial than choosing one over the other. The girls' ways of thinking, seeing and interacting with those around them are complex and he learns from their combined wisdom how to navigate challenges and trials. Criticism focusing primarily on the secondary character of Luna is relatively scarce, despite her impact on Harry's views regarding death and the afterlife. This thesis offers a new perspective on the importance to Rowling's narrative of this open-minded, idiosyncratic figure. Rational and imaginative ways of thinking are necessary modes to use in the resistance to prejudice in wizarding society since this pervasive privileging of wizards over other magical beings espoused by the magical government inspires Lord Voldemort to kill or subjugate those whose magical heritage falls short of pure-blooded wizarding ancestry. In analysing the ostensibly conflicting rational and imaginative modes of thought, I examine Rowling's unconscious use of shadow theory through her treatment of Harry's dreams and visions "“ a direct connection between Harry and Lord Voldemort. Harry confronts his antagonist "“ and addresses the prejudices pervading wizarding society "“ through making rational decisions that require imaginative action.
Keywords: Potter, Harry (Fictitious character); Rowling, J. K. -- Characters -- Harry Potter; Rowling, J. K. -- Criticism and interpretation; Fantasy fiction, English -- History and criticism; Magic in literature; Wizards in literature; Rationalism in literature; Imagination in literature; Prejudices in literature